PENINGKATAN PEMAHAMAN PARA PELAJAR TENTANG PELANGGARAN HAK CIPTA TERHADAP KARYA TULIS DAN BUKU DI SMK NEGERI 5 KECAMATAN SEMARANG TIMUR KOTA SEMARANG - Kridasaksana, Doddy (Fakultas Hukum Universitas Semarang, 2022)
The existence of scientific work can not be denied a necessity , especially for students in the learning process . It is no exaggeration to human intellectual creations are given adequate legal protection . In the reality of life , people should understand Copyright protection . Members of the public, in this case students who are users required to book and paper in receiving education and teaching process should also understand Copyright protection . The fact that happened, it did not show it. One indicator of the observations of many businesses seem photocopy especially around schools that readily accept a photocopy papers and books in the form of a whole , as well as the tendency of reluctance to buy original books . If this is left alone then this condition is very detrimental to the authors and publishers because of their disadvantaged economic rights, anda moral rights. The objectives of this service is to provide accurate and correct information to the public, especially the students about the laws regarding Copyright ( According to Law 28 of 2014 ) , to give more information about many kind of against Copyright Infringement Writing and Books. The benefits of this activity is conducted for the students to know more about Copyright Infringement on Writing and Books. The results of the implementation indicates that , prior to the implementation of activities, vocational school students do not understand the SMK 5 Semarang and understand, and after vocational school counseling students SMK 5 Semarang increased insight about Copyright Infringement on Writing and Books. It is characterized by the number of responses in the form of questions and seriousness in accepting the material provided